STUDI TEORI FRAUD HEXAGON TERHADAP FRAUDULENT FINANCIAL STATEMENT PADA PERUSAHAAN YANG TERGABUNG DALAM INDEKS KOMPAS100 DI BURSA EFEK INDONESIA - Verenn Tanuwijaya; Lauw Sun Hiong; Febriana Louw; Nopiani Indah (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2022)
This study aims to determine the effect of the fraud hexagon on financial statement fraud in companies indexed by Kompas100 on the Indonesia Stock Exchange. In this study, pressure was measured by return on assets, measured by the BDOUT ratio, rationalization was measured using independent auditor changes, capability was measured by CEO change, arrogance was measured by CEO duality, collusion was measured by government cooperation projects, and fraudulent financial statements were measured by M-score. The data analysis technique used descriptive statistical analysis, classical assumption test, logistic logistics, model test and coefficient of determination as well as hypothesis testing which was carried out using the SPSS analysis tool. The result of this research is that the fraud hexagon has no effect on financial statement fraud.